Heat treatment of aluminum extrusion dies and study of their heating by convection/radiation - Miguel Oliveira (2015)
This paper shows the study of the heating phase of the quenching procedure of dies in steel ALVAR 14 (DIN 56 NiCrMoV7) for the extrusion of aluminum. The heat treatment was executed in BMI vacuum hardening furnaces (model B84T) at the company F. Ramada, A double dagger os e IndA(0)strias, S.A. The die had the shape of a massive disk and its heating was studied experimentally, by measuring and recording the relevant temperatures along the time using thermocouples, and was also studied analytically and numerically using the ABAQUS software. The experimental average convective heat transfer coefficient between the gas and the disk was found to be 10 W/(m(2) K), with the convective heating representing 22 % of the total energy supplied to the disk. The coefficients of heat transfer by radiation found at the initial and final stages of the heating process ranged between 3 and 64 W/(m(2) K), respectively, and were determined using the lumped system analysis in conjunction with experimental data. By acting essentially upon the apparent emissivity of the disks, it was possible to fit the numerically simulated heating curve of the disk to the experiments. The maximum value of the global heat transfer coefficient to the disk was fairly low, 64 W/(m(2) K), resulting on Biot numbers below 0.1, and thus allowing the use of lumped system analysis. These Biot numbers also indicate that the temperature gradients inside the dies are smaller than expected, enabling the use of higher heating rates that reduces the total time and costs of the quenching treatment.